Analisis Keandalan Sistem Transfer Bulk Menggunakan Metode Reliability Centered Maintenance (RCM) - Erwin Sutantyo; Purwanto Purwanto; Rahindra Bayu Kumara; Widar Bayu Wantoro; Irsat Surya Sekti; Wahyu Ari Putranto (Infotekmesin, 2026)
The Bulk Transfer System on Supply Vessels plays a crucial role in supporting offshore logistics, particularly in transferring bulk cement to drilling facilities. The system operates on pneumatic principles and is influenced by compressors, piping networks, mechanical components, and control devices. However, the current maintenance approach remains reactive, increasing the risk of recurring operational failures. This study aims to evaluate system reliability and determine an optimal risk-based maintenance strategy using Reliability Centered Maintenance (RCM). The analysis includes system function identification, Failure Mode and Effect Analysis (FMEA), and Logic Tree Analysis (LTA). The results show that the transfer pipeline has the highest risk (RPN 48), followed by the air compressor unit, air receiver tank, and safety system (RPN 36). LTA indicates that most failures are evident with Operational Consequences, while safety system failures are categorized as Safety Consequences. The application of RCM effectively improves overall system reliability.